The Ideology of Urban Teenage Life in Facing Globalization (Law Research Review Quarterly, 2016)
Ideology is something that is very vital for a nation. The identity of a nation starts from their understanding of the ideology they hold. Without ideology, a nation will not have a way of life and will be easily influenced by negative influences from both outside and inside. The ideology of a nation cannot be separated from the young generation of a nation. The young generation as the next generation of the nation has an important role in maintaining and realizing this ideology in the life of the nation and state. The next generation of the nation referred to here is teenagers. Teenagers are the beginning of a golden phase for an ideology to be implanted. Because in the teenage phase, ideology can be better understood and implemented by them until they are adults. But in the development of increasingly advanced times, coupled with the current globalization, can have an impact on the ideology of adolescents today. Especially the life of adolescents who are in urban areas. That is because, urban is a very strategic place for globalization to develop and influence the ideology of the lives of adolescents. Observation and analysis of the ideology of urban youth life is needed in the face of globalization. It is very necessary to know the effects that arise. Whether it's a positive impact, or a negative impact on the ideology of urban youth. Efforts to reduce the negative impact caused.